Gambaran Kasus Entropion Involusional di Sultan Agung Eye Center (SEC) Rumah Sakit Islam Sultan Agung Semarang Tahun 2008-2018 - INDRAJATI, Christina; WIDIYANTO, Bagas (Media Farmasi Indonesia, 2020)
Involutional entropion is an eye disorder that often occurs because of the aging process. The most severe complication of this case is the permanent decrease in vision caused by corneal damage due to friction of the eyelid. This study aims to provide an overview of involutional entropion at the SEC Sultan Agung Islamic Hospital Semarang. The research method used was descriptive observational. Research subjects were 69 patients diagnosed with involutional entropion from January 2008 until January 2018. 69 research subjects were used, divided into several characteristics. Gender, 36.2% males, and 63.8% female. Age group, <60 years 31.9% and> 60 years 68.1%. The location of the eyelids, the upper eyelid 40.6%, and the lower eyelid 59.4%. Operating techniques, ALR (Anterior Lamelar Reposition) 40.6%, Everting Suture technique 29.0%, Weis technique 30.4%. Results of surgery recovered 86.2% and recurring 13.8%.